Facile synthesis of arylated heterofullerenes ArC59N - Nuber, Berthold; Hirsch, Andreas (Chemical Communications, 1998)
The thermal treatment of the heterofullerene dimer (CN) with anisole, toluene and 1-chloronaphthalene in the presence of toluene-p-sulfonic acid and air leads to the formation monoarylated azafullerenes ArCN in very good yields.